Highly Flexible and Stretchable Nanowire Superlattice Fibers Achieved by Spring‐Like Structure of Sub‐1 nm Nanowires. (28th July 2019) - Zhang, Simin; Lin, Haifeng; Yang, Haozhou; Ni, Bing; Li, Haoyi; Wang, Xun
Abstract: Conventional inorganic nanowire (NW) fibers are usually not stretchable and elastic, which may limit their practical applications. Inspired by the similarity between inorganic sub‐1 nm NWs and polymer chains in dimension, and helical spring‐like structure of cellulose in cherry bark, highly flexible and stretchable NW superlattice fibers composed of sub‐1 nm GdOOH NWs are fabricated. The NW fibers could be twined, bent, twisted, and tied without any damage. When the strain is less than 10%, the fibers present elastic deformation. The elongation at break of the fibers usually reaches ≈40–50% and the highest elongation could reach ≈86%. Excellent flexibility and stretchability of the NW fibers are attributed to the well‐aligned spring‐like NWs assembled superlattice, which are demonstrated by scanning electron microscopy tests, synchrotron small‐angle X‐ray scattering, and obvious birefringence. Moreover, NW‐nanoparticle (NP) fibers are fabricated, inspired by inorganic nanoparticle–reinforced polymers. The strength is improved compared with the NW fibers. Based on this work, it is possible to fabricate multifunctional, flexible, and stretchable inorganic NW materials composed of different inorganic sub‐1 nm NWs, which may be useful in practical applications. Abstract : Highly flexible and stretchable nanowire (NW) superlattice fibers are fabricated through a wet‐spinning method, composed of well‐aligned spring‐like sub‐1 nm GdOOH NWs. The strength of the fibers is improved by adding some ultrathin nanoparticles. Based on this, it is possible to fabricate various flexible and stretchable NW fibers, which may be useful in practical applications.